Mechatronics and Robotics Engineering for Advanced and Intelligent Manufacturing - Zhang, Dan.; Wei, Bin.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Featuring selected contributions from the 2nd International Conference on Mechatronics and Robotics Engineering, held in Nice, France, February 18-19, 2016, this book introduces recent advances and state-of-the-art technologies in the field of advanced intelligent manufacturing.  This systematic and carefully detailed collection provides a valuable reference source for mechanical engineering researchers who want to learn about the latest developments in advanced manufacturing and automation, readers from industry seeking potential solutions for their own applications, and those involved in the robotics and mechatronics industry.
Keywords: Mechatronics; Industrial organization; Control engineering; Robotics; Automation; Manufactures; Artificial intelligence; Mechatronics; Industrial Organization; Control, Robotics, Automation; Machines, Tools, Processes; Artificial Intelligence